Accounting Practices Based on Memory in the Tofu and Tempe Business: Praktik Akuntansi Berbasis Ingatan dalam Bisnis Tahu dan Tempe (Indonesian Journal of Cultural and Community Development, 2024)
General background accounting is often perceived as merely a set of recording and bookkeeping techniques, limiting its broader scope. Specific background in reality, various factors such as social, economic, cultural, legal, and political elements influence the development of accounting practices in local businesses. Knowledge gap among micro-businesses, like tofu and tempe entrepreneurs in Sepande Village, accounting practices remain underexplored, especially in relation to cultural influences.This research aims to describe the interaction between cultural meanings and accounting practices in the tofu and tempe business. Results the findings reveal that these entrepreneurs do not maintain formal accounting records due to perceived complexity and a lack of necessity. Instead, they rely on memory and experience to manage their finances. Cultural and societal characteristics play a significant role in decision-making, shaping a unique form of accounting that deviates from conventional methods. Novelty this study contributes new insights into how informal accounting practices emerge in a culturally embedded business environment, where memory replaces traditional accounting systems. Implications the results highlight the importance of understanding the cultural context when developing accounting education and systems for micro-businesses, suggesting that a one-size-fits-all approach to accounting may not be effective across different cultural settings.Highlights: • Entrepreneurs rely on memory for financial management instead of formal records.• Cultural characteristics significantly influence business decision-making processes.• Informal accounting practices emerge from the unique cultural context of the community.Keywords: Accounting, Culture, Micro-businesses, Tofu, Tempe